A study on the impact of economic growth, interest rate and inflation rate on private savings in Malaysia / Norashikin Ibrahim - Ibrahim, Norashikin (2007)
This study conducted to examine the private savings behavior in Malaysia. This study further examines the relationship between economic growth, interest rate, and inflation rate with the private saving in Malaysia. This study done on this topic as the private savings said to be affected by the three economic variables and less study undertaken regarding this topic in Malaysia. It also become essential issue in Malaysia as private savings is a major source of fund and capital and Malaysia is one of the largest saving countries in world. All data used are in yearly basis range from year 1972 until 2005. Using the Multiple Linear Regression, this study reveals that none the variables examine is significant to the private savings in Malaysia.